2017
DOI: 10.1371/journal.pntd.0005598
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing distinguishes between relapse and reinfection in recurrent leprosy cases

Abstract: BackgroundSince leprosy is both treated and controlled by multidrug therapy (MDT) it is important to monitor recurrent cases for drug resistance and to distinguish between relapse and reinfection as a means of assessing therapeutic efficacy. All three objectives can be reached with single nucleotide resolution using next generation sequencing and bioinformatics analysis of Mycobacterium leprae DNA present in human skin.MethodologyDNA was isolated by means of optimized extraction and enrichment methods from sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…It is interesting to note that recurrent patient #1126 presented allelic and genotypic global counts similar to the controls and in contrast with the two other recurrent individuals. Patient #1126 has been described previously as the only case of recurrence caused by distinct M. leprae strains isolated in the first and the second diagnosis 8 . Also, patient #1126 presented the shortest time to relapse and the latest age of diagnosis -32 years -similar to the controls (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that recurrent patient #1126 presented allelic and genotypic global counts similar to the controls and in contrast with the two other recurrent individuals. Patient #1126 has been described previously as the only case of recurrence caused by distinct M. leprae strains isolated in the first and the second diagnosis 8 . Also, patient #1126 presented the shortest time to relapse and the latest age of diagnosis -32 years -similar to the controls (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Based on comparative analysis between M. leprae genomes obtained in the first and second infection of each patient, the authors concluded for two cases of relapses caused by same strain and one case of reinfection caused by a different M. leprae strain 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, the sole source of M. leprae DNA suitable for genomics was from bacteria isolated 12 months after infection of armadillos or mice. Recently, we have developed and optimized methods that enable M. leprae DNA to be extracted directly from fresh or formalin-fixed skin biopsies from leprosy patients 28 . These methods include enrichment of M. leprae DNA by array capture 17 but this is less practical for large population-based investigations.…”
Section: Resultsmentioning
confidence: 99%
“…RpoB numbering is based on M. leprae , E. coli numbering in brackets: 51 (126), 52 (127), 171 (246), 200 (275), 432 (507), 433 (508), 441 (516), 448 (523), 451 (526), 456 (531), 681 (756), 791 (866). 1 Coverage below the threshold, both “2188” isolates come from the same patient but after an interval of 7 years 28 …”
Section: Resultsmentioning
confidence: 99%